Design and enhancement of microstrip patch antenna with frequency selective surface backing for vehicle-to-vehicle communication - Troudi, Ikram; Baccouch, Chokri; Belgacem Chibani, Rhaimi (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This research investigates the application of frequency selective surface (FSS) reflectors to enhance vehicle-to-vehicle (V2V) communication performance. A compact antenna measuring 32×24×1.6 mm, derived from an FSS 10×10×1.6 mm unit cell, was studied. Integration of FSS technology with the antenna resulted in significant performance improvements. The gain increased from 3.9 to 5.4 dB at 5.9 GHz, representing a 1.5-fold enhancement. Additionally, the bandwidth extended to 230.94 MHz. These advancements demonstrate the efficacy of FSS technology for antenna gain enhancement in V2V systems. The compact design, coupled with improved performance, makes this approach particularly suitable for vehicular applications where space is limited. This study not only showcases the potential of FSS technology in antenna design but also suggests its broader applicability in enhancing V2V communication systems, potentially contributing to the development of more efficient and safer transportation networks.